Exploring the Intricacies of Skull Anatomy of Common Crow (Corvus splendens) - Nagarajan, Hemavathi; Sengodan, Abinaya; Sengottuvel, Jayachitra; Kannan , Thandavan Arthanari (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted on skull bone of common crow (Corvus splendens) to understand the gross morphological anatomy  of the bones and its articulations in depth. The Common crow’s carcasses were brought to the department of Veterinary Anatomy of  the Institute, and bones were collected after maceration. The skull of common crow was composed of 11 paired and 6 unpaired bones.  Occipital, sphenoid, ethmoid, mandible, vomer and hyoid bones were unpaired. Temporal, parietal, frontal, lacrimal, nasal, premaxilla,  maxilla, zygomatic, palatine, quadrate and pterygoid bones were paired. The skull of common crow lacked interparietal bone. The bones  were divided as neurocranial and viscerocranial groups. Skull length, skull width, height of cranium, viscera-cranial length, upper beak  width, lower beak length and lower beak width were measured and skull index, cranial index, facial index and foramen magnum index  were calculated. The findings of this study would be a reference material for the upcoming researches on Corvidae family.
Keywords: Common crow; Corvidae; Neurocranium; Viscerocranium; Skull anatomy